Genetic parameters for earnings in Quarter Horse - Silva, A.P.A.; Curi, R.A.; Langlois, B.; Silva, J.A.II.V. (Genetics and molecular research, 2014)
In this study, we estimated the heritability (h(2)) of earnings in the Quarter Horse in order to evaluate the inclusion of this trait in breeding programs. Records from 14,754 races of 2443 horses from 1978-2009 were provided by Sorocaba Hippodrome, São Paulo, Brazil. All ancestors of the registered horses were included in the pedigree file until the 4th generation. Log-transformed performance measures (LPM) were analyzed for animals aged 2, 3, and 4 years and during their entire career. The h(2) estimates were obtained using a multi-trait model and Gibbs sampling that included the effects of sex, year of race, and animal in all analyses. Five analyses were performed: 1 in which LPM was divided by the number of prizes, 1 in which LPM was divided by the number of race starts, and 3 analyses that included the number of prizes, number of race starts, and both (LPM_cNPS) as covariates. Analysis was performed with and without inclusion of the maternal effect. Models were compared based on the deviance information criterion and LPM_cNPS including maternal effects was found to be the best model. The h(2) estimates and standard deviation obtained using model LPM_cNPS were 0.19 ± 0.08, 0.21 ± 0.08, 0.22 ± 0.09, and 0.21 ± 0.07 for earnings at 2, 3, and 4 years of age and total career, respectively. Our analyses indicate that earnings are subject to selection and can be included in breeding programs to improve the racing performance of Quarter Horses.